Determinants of Credit Growth to Nonfinancial companies in B&H - Alihodzic, Almir A.; Plakalović, Novo (Industrija, 2016)
Non-financial sector in B&H and the companies due to lack of its own funds for sustainable growth rely on financing its operations through bank loans. The dominant share of lending to banks in B&H is directed to the household sector while on the other hand the approval of bank loans to enterprises is on a smaller scale. Corporate sector due to underdeveloped capital markets is not able to borrow through the issuance of equity and debt securities. The main objective of this study is to determine which independent variables in the regression models have an impact on the amount of approved loans granted by banks to non-financial sector, i.e. companies. The loans growth rate will be observed as a dependent variable, and the growth rate of non-performing loans, the growth rate of operating costs, real GDP growth, consumer price index, deposit growth rate, deposit interest rate, interest rate (EURIBOR), and interest rate (LIBOR) will be used as independent variables. Non-financial sector in B&H and the companies due to lack of its own funds for sustainable growth rely on financing its operations through bank loans. The dominant share of lending to banks in B&H is directed to the household sector while on the other hand the approval of bank loans to enterprises is on a smaller scale. Corporate sector due to underdeveloped capital markets is not able to borrow through the issuance of equity and debt securities. The main objective of this study is to determine which independent variables in the regression models have an impact on the amount of approved loans granted by banks to non-financial sector, i.e. companies. The loans growth rate will be observed as a dependent variable, and the growth rate of non-performing loans, the growth rate of operating costs, real GDP growth, consumer price index, deposit growth rate, deposit interest rate, interest rate (EURIBOR), and interest rate (LIBOR) will be used as independent variables.